(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
Psoriasis is a T-cell mediated chronic inflammatory diseases where pro-inflammatory mediators are involved in its pathogenesis. Alpha-2-macroglobulin (α-2M) is a panproteinase inhibitor having unique clearing role of different cytokines. This study was conducted on 30 patients with moderate to severe psoriasis to see the plasma level of α-2M and was compared with the normal healthy controls. Patients who were already selected for systemic treatment (methotrexate) and consented for routine blood test for monitoring at baseline and 12 weeks after treatment were enrolled along with 10 healthy controls. The venous blood (5 mL) was collected and the plasma alfa-2 macroglobulin was estimated using the enzyme-linked immunosorbent assay. The mean plasma α-2M level was 3.0 ± 0.4 g/L among the normal healthy persons, and 2.8 ± 0.7 g/L among the untreated patients of psoriasis (p>0.05). Its level among the patients with psoriasis after systemic antipsoriatic drugs was 2.8 ± 0.6 g/L which was not significantly different from the baseline level (p>0.05). The study shows that the plasma α-2M level in psoriasis is not different comparing with normal healthy persons.